Penegakan Hukum terhadap Penyalahgunaan Tindak Pidana Narkotika - I Gede Darmawan Ardika; I Nyoman Sujana; I Made Minggu Widyantara (Warmadewa Press, 2020)
Drug abuse from year to year has always been increasing, not only in adults but also among adolescents and children. The cause of this abuse consists of two factors, namely internal and external factors. With these problems, this study aims to determine the regulation of criminal sanctions against narcotics abuse and to find out the application of criminal sanctions against narcotics abuse. This research uses the normative method. Sources of data used are sources of secondary legal materials obtained through document, and analysis of legal materials using legal arguments. The results of the study show that the sanctions against narcotics abuse are regulated in Law Number 35 of 2009 concerning Narcotics Articles 111 to 148. Then, criminal sanctions against narcotics abuse are in the form of imprisonment and fines. The criminal system against narcotics abusers uses a double track system, namely implementing criminal sanctions and sanctions for action at once